Factors Affecting Online Purchase Intention on Social Media Users During the Pandemic in Jakarta - Andi Muhammad Sadat; Basrah Saidani; Sholikhah; Kattareeya Prompreing (Universitas Nahdlatul Ulama Sidoarjo, 2023)
This study analyzes the factors influencing online purchase intention among social media users in Jakarta during the Covid-19 pandemic. In the literature, many variables can be used to explain the phenomenon of online purchases. However, this research is limited to the main variables such as social media marketing, customer trust, e-Word of mouth, brand image, and online customer reviews. The data collection method was carried out through a questionnaire with a purposive sampling technique via a google form, which was distributed using social media networks, namely WhatsApp group and Facebook, which are popular platforms in the country. The relationship of each independent variable to the dependent variable was tested using the structural equation modeling (SEM) technique using Smart PLS version 3. A total of 238 sample units spread across the DKI Jakarta area were successfully collected and processed. The results of the data analysis show that of the five hypotheses proposed, only one is significant, namely, online customer reviews have a significant relationship to online purchase intention during the Covid-19 pandemic in DKI Jakarta.